Estressores e coping de crianças e adolescentes com Transtorno do Espectro Autista na percepção dos pais - Garcia, Mariana Grassi Maciel (2021)
Autism Spectrum Disorder (ASD) belongs to the category of neurodevelopmental disorders and is characterized by deficits that lead to impairments in personal, social, and academic or professional functioning. These deficits may range from specific limitations in learning, language, communication, behavior, and control of executive functions to global impairments in cognitive and social skills. Considering the impact of this condition on families, this study aimed to analyze stressors and coping strategies of the ASD condition in children and adolescents. The research was conducted entirely remotely, fromthe recruitment of participants to the data collection session, conducted through a digital platform, lasting approximately 1 hour. The sample was composed of 10 mothers, being the children and adolescents, aged between 8 and 12 years old, diagnosed with ASD. This identification was made from the contact with the participants. The following instruments were applied: 1) sample characterization form; 2) Brazil Economic Classification Criterion; 3) Child Behavior Checklist (CBCL); 4) Stressors Questionnaire, prepared for this study, parent or guardian version; 5) adapted Instrument for the Evaluation of Coping Strategies of Children and of Adolescents with ASD (IC-TEA), parent or guardian version. The Sample Characterization Form and the CBCL were applied through an electronic form, together with the Informed Consent Form. The other instruments were applied through a digital platform. The data were categorized and submitted to descriptive statistical analysis and qualitative analysis. A clinical profile was verified for total competence and for most behavior problems, according to data from the CBCL. Dealing with several commands at the same time; being in a noisy environment and change of routine were the most cited stressors and the analysis of coping indicated maladaptive strategies for most of these stressors. It is considered that the research may contribute to a better understanding of the stressors in the sample, seeking to guide initiatives for parental guidance programs and professional interventions focused on more adaptive coping strategies.